2016
DOI: 10.3923/pjbs.2016.289.298
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activity Alterations of Human Amniotic Membrane Pre and Post Irradiation Tissue Banking

Abstract: Viable HAM was featured with biological activity than fixed HAM prepared by irradiation tissue banking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…This result was also confirmed by Nemr et al (2016) who reported that, gamma irradiation of HAM at a dose of 25kGy affects the quality of the extracted RNA and causes completely degradation of RNA molecules. It is known that intact RNA only presented in metabolic active cells.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…This result was also confirmed by Nemr et al (2016) who reported that, gamma irradiation of HAM at a dose of 25kGy affects the quality of the extracted RNA and causes completely degradation of RNA molecules. It is known that intact RNA only presented in metabolic active cells.…”
Section: Discussionsupporting
confidence: 76%
“…Also, many of clinical trails using amniotic membrane as a biological bandage were published for curing some of skin disorders and ulcers. This is due to several biological benefits revealed by amniotic membrane such as being a nonimmunogenic material, having antimicrobial activity and inducing cellular renewing and growth (Nemr et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Human amniotic epithelial cells (HAECs) were isolated from HAM using a method described previously. 7 About 5×10 6 of HAECs were plated into T-25 cell culture flask that contains 5 mL DMEM: F12 medium supplemented with 10% fetal bovine serum (Lonza, Alpharetta, GA, USA). Cultures were free from further additives such as antibiotics, antimycotics, growth factors, feeder cells, or other stimuli.…”
Section: Antimicrobial Test Of Haecs Secretionsmentioning
confidence: 99%